Genetic diversity of antigen 38 kDa in Mycobacterium tuberculosis strains from China. (May 2018) - Du, Yingzhen; Li, Hongxia; Qin, Xuebing; Wang, Yan; Zhang, Zhijian; Qu, Geping; Fang, Xiangqun; Yu, Senyang
Abstract: We used 335 Mycobacterium tuberculosis strains from 2010 National Epidemiologic Survey for TB in China and performed comparative sequence analysis of 38 kDa gene after amplification. From the results, we found that there were 5.07% M.tuberculosis strains that demonstrated genetic diversity of 38 kDa in China, and 2.99% strains showed polymorphism of the 38 kDa antigen, and this may be the reason for changes in the antigen produced, which may in turn cause alterations of related functions, thereby allowing immune evasion.